The strategic planning in learning styles for Qur’anic memorization schools in Nigeria - Auwal Salisu (Journal of Islamic Business and Economic Review, 2020)
Many Quranic schools and camps for teaching Qur’anic recitation have expended enormous resources and energy in trying to draft and produce a standard syllabus for the memorization of the Holy Qur’an in their respective schools nationwide. A number of these schools are graduating excellent Qur’anic reciters using the syllabus (Adam, 2012). But in Nigeria, hundreds of Tahfiz schools are exiting with or without specific blue print of Tahfiz governing principles, talk less of strategic planning and future developmental plan.